2014
DOI: 10.1155/2014/583794
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Bleeding Patient Receiving New Oral Anticoagulants: A Role for Prothrombin Complex Concentrates

Abstract: Ease of dosing and simplicity of monitoring make new oral anticoagulants an attractive therapy in a growing range of clinical conditions. However, newer oral anticoagulants interact with the coagulation cascade in different ways than traditional warfarin therapy. Replacement of clotting factors will not reverse the effects of dabigatran, rivaroxaban, or apixaban. Currently, antidotes for these drugs are not widely available. Fortunately, withholding the anticoagulant and dialysis are freqnently effective treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…62 The aPCC FEIBA has been documented in a series of case reports to successfully and rapidly resolve dabigatran-related life-threatening bleeding complications. 39,[63][64][65] In a porcine polytrauma model with supratherapeutic dabigatran concentrations, FEIBA in doses ranging from 25 to 50 IU/kg was found to reduce blood loss in a dose-dependent manner, with the 50-IU/kg dose effectively reducing blood loss without inducing a procoagulant state. 66 In a case series of four patients who experienced bleeding while receiving dabigatran (intracranial hemorrhage [ICH], n = 2; pericardiocentesis, n = 1; gastrointestinal, n = 1), FEIBA doses ranging from 42 to 100 IU/kg were successful in stabilizing the patients' condition without any subsequent thrombosis observed.…”
Section: S19mentioning
confidence: 95%
See 2 more Smart Citations
“…62 The aPCC FEIBA has been documented in a series of case reports to successfully and rapidly resolve dabigatran-related life-threatening bleeding complications. 39,[63][64][65] In a porcine polytrauma model with supratherapeutic dabigatran concentrations, FEIBA in doses ranging from 25 to 50 IU/kg was found to reduce blood loss in a dose-dependent manner, with the 50-IU/kg dose effectively reducing blood loss without inducing a procoagulant state. 66 In a case series of four patients who experienced bleeding while receiving dabigatran (intracranial hemorrhage [ICH], n = 2; pericardiocentesis, n = 1; gastrointestinal, n = 1), FEIBA doses ranging from 42 to 100 IU/kg were successful in stabilizing the patients' condition without any subsequent thrombosis observed.…”
Section: S19mentioning
confidence: 95%
“…S18 [39][40][41][42][43][44][45][46][47][48][49][50] One analysis, however, suggested that activated PCCs (aPCCs) and rFVIIa were more likely to produce partial dabigatran reversal than nonactivated PCCs. 51 Beyond FFP and rFVIIa, three types of PCC products are currently available.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of circulatory instability the usual vasopressors are used, while patients receiving massive transfusions may require plasma/plate let products and fibrinogen concentrates (5,6). Should conventional measures prove inadequate, offlabel administration of prothrombin complex concentrates or activated prothrombin complex concentrate and/or recombinant factor VIIa (rFVIIa) in the recommended dosages can be considered (5,6,22,23,(27)(28)(29)(30) (Figure 2). In experimental studies (dabigatran) and tests on healthy volunteers (apixaban, edoxaban, and rivaroxaban), the best effect has been documented for prothrombin complex concentrate (29-32, e27-e33); no prospective randomized trials have been conducted.…”
Section: Management Of Major/life-threatening Hemorrhagementioning
confidence: 99%
“…47 Furthermore, in volunteers given edoxaban, 4-factor PCC attenuated bleeding from punch biopsy sites in a concentration-dependent manner. 48 With 50 U/kg, PCC restored bleeding duration to background levels and enhanced thrombin generation.…”
mentioning
confidence: 99%